Subdural Hemorrhage and Antithrombotic Therapy - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at the Mott Children's Hospital, Ann Arbor, MI, report 4 infants with diffuse brain injury and cerebral atrophy who developed cerebral venous sinus thrombosis and were treated with the low-molecular-weight heparin, enoxaparin.